Characterization of model compounds and poly(amide-urea) urethanes based on amino acids by FTIR, NMR and other analytical techniques. (July 2017) - Chan-Chan, Lerma H.; González-García, Gerardo; Vargas-Coronado, Rossana F.; Cervantes-Uc, José M.; Hernández-Sánchez, Fernando; Marcos-Fernandez, Angel; Cauich-Rodríguez, Juan V.
Graphical abstract: Highlights: Poly(amide-urea)urethanes can be prepared withl -arginine, glycine andl -aspartic acid as chain extenders. Model compounds were useful to confirm reaction of amino acids via urea and amide formation. Polymers exhibited different physicochemical and mechanical properties depending on the chain extender used. Abstract: The synthesis of novel polyurethanes is a subject of increasing interest, especially those that involve biologically active molecules. Generally, the reports on the synthesis of segmented polyurethanes using modified amino acids as chain extenders assume that the reaction occurs due to functionalities (OH and NH2 ) of the last compounds. However, few works really prove the reaction takes place with unmodified amino acids. In this work, spectroscopic techniques such as 1 H, 13 C, and 1 H-1H COSY NMR and FTIR were used to chemical characterization of poly(urea-amide) urethanes synthesized from polycaprolactone diol (PCL diol 530), 4, 4′-methylene-bis(cyclohexyl isocyanate) (H12 MDI), and amino acids such asl -arginine, glycine orl -aspartic acid as chain extenders. In addition, model compounds (without PCL diol) were analyzed to confirm reaction of amino acids via urea and amide formation. Additionally, the polymers exhibited different physicochemical and mechanical properties depending on the chain extender used. These results suggest that unmodified amino acids can be used as chain extenders in the synthesis of poly(amide-urea) urethanes for biomedical applications.